Iron partitioning at an early growth stage impacts iron deficiency responses in soybean plants (Glycine max L.) - Santos, Carla S.; Roriz, Mariana; Carvalho, Susana M. P.; Vasconcelos, Marta W. (Frontiers in Plant Science, 2015)
Iron (Fe) deficiency chlorosis (IDC) leads to leaf yellowing, stunted growth and drastic yield losses. Plants have been differentiated into ‘Fe-efficient’ (EF) if they resist to IDC and ‘Fe-inefficient’ (IN) if they do not, but the reasons for this contrasting efficiency remain elusive. We grew EF and IN soybean plants under Fe deficient and Fe sufficient conditions and evaluated if gene expression and the ability to partition Fe could be related to IDC efficiency. At an early growth stage, Fe-efficiency was associated with higher chlorophyll content, but Fe reductase activity was low under Fe-deficiency for EF and IN plants. The removal of the unifoliate leaves alleviated IDC symptoms, increased shoot:root ratio and trifoliate leaf area. EF plants were able to translocate Fe to the aboveground plant organs, whereas the IN plants accumulated more Fe in the roots. FRO2-like gene expression was low in the roots; IRT1-like expression was higher in the shoots; and ferritin was highly expressed in the roots of the IN plants. The efficiency trait is linked to Fe partitioning and the up-regulation of Fe-storage related genes could interfere with this key process. This work provides new insights into the importance of mineral partitioning among different plant organs at an early growth stage.